(untitled) (Research, Society and Development, 2020)
Diabetes mellitus is a growing and important health problem for all countries. Frequently related to diabetes are the highest rates of hospitalization, as well as greater need for medical care, higher incidence of cardiovascular and cerebrovascular diseases, blindness, renal failure and non-traumatic lower limb amputations.The polar portion of A. esculentus, known as okra water, provides a large amount of soluble fiber. Studies show a large decrease in glycaemia in rats treated with okra. The present work aims to analyze the effects of okra on the glycemic indexes of rats with diabetes mellitus. For the analysis of the aforementioned okra effects, experiments were performed on 21 rats, from the vivariumof the Facid Differential Faculty | Wyden of Wistar rats (Rattus Norvegicus), aged between 30 and 60 days, of both sexes and with average weight of 200 to 250g. The random distribution of the rats occurred in order to form three groups - A, B, C. All rats were induced to diabetes, however, only those from group B received okra water, those from group C water of okra associated with glibenclamide 5mg, serving group A as a control group, which received only water. At the end of the study it was possible to observe that the use of A. esculentus fibers is able to improve the glycemic profile of rats with DM2.However, the association of fibers with glibenclamide prevents the hypoglycemic action of the fibers and the oral antidiabetic agent.